A new synthesis aperture-MUSIC algorithm for damage diagnosis on complex aircraft structures. (February 2020) - Bao, Qiao; Yuan, Shenfang; Guo, Fangyu
Highlights: We propose a new synthesis aperture-MUSIC algorithm for damage diagnosis. The omnidirectional array errors are estimated to compensate steering vectors. Experimental results on an aircraft reinforced panel prove the proposed method. Abstract: Multiple signal classification (MUSIC) algorithm has gradually been applied to guided wave based structural health monitoring (SHM) as a novel promising method, which is able to realize directional scanning and has the potential to monitor multiple signal sources. However, on complex structures, the low signal-to-noise ratio (SNR) of damage scattered signals and structural anisotropy usually result in the poor localization performance of MUSIC algorithm based damage diagnosis method. To solve these problems for applying the MUSIC algorithm on complex structures, this paper presents a new synthesis aperture-MUSIC algorithm for damage diagnosis with array error compensation. This method enhanced the damage scattered signals and compensate the phase delay perturbations caused by structural anisotropy, which realized damage localization on complex structures. The proposed method is verified on an aircraft structure with T-stiffeners, ribs and rivets to detect corrosion damages with five severity levels. Application results show the advantage and effectiveness of the presented method.